PENERAPAN MODEL PEMBELAJARAN SQ4R PADA MATERI MOMENTUM DAN IMPULS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X IPA SMA NEGERI 6 PEKANBARU - Sari, Maissy Emelya; Nor, Muhammad; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the improvement of critical thinking skills in learning physics by applying SQ4R learning model. This research was conducted at SMA Negeri 6 Pekanbaru in January to May 2018. The population in this study is the students of class X IPA semester 2 of the year 2017/2018 which consists of 6 classes. The sample in this study were 2 randomly selected homogeneous classes, ie X IPA 1 as the experimental class and X IPA 3 as the control class. The design of this research is Quasi Experimental in the form of Nonequivalent Control Group Design. Instrument of data collection in this research is critical thinking ability test which consist of 12 items of multiple choice by using descriptive analysis and inferential analysis using T test (independent samples t-test). Based on the descriptive analysis, the result of the average absorption of students in the class that applied the SQ4R learning model get the pretest score of 35.78% with the less good category and the posttest score of 64.22% with good enough category. While in the class that apply conventional learning get absorbed average class 38,48% with less good category at pretest score and 54,66% with category good enough at posttest score. The critical thinking ability of the classroom students applying the SQ4R learning model is in the moderate category with N-Gain 0.45 while the class applying the conventional learning is 0.27 with the low category. Based on inferential analysis through independent samples t-test obtained Sig value. (2-tailed) = 0.001 <0.05 which means there is a significant difference. The results of this study can be concluded that the use of SQ4R learning model can improve students' critical thinking skills in SMA Negeri 6 Pekanbaru on the material Momentum and Impuls.Keywords: Critical Thinking Skill, SQ4R (Survey, Question, Read, Reflect, Recite, Review) Model